
2
This notation is supposed to express Linear Omega Level intuitively, so don't expect it to go any higher.
a[c]b is supposed to be is an array.
a[#,1]b=a[#]b
a[#,n,m]b=a[#,a[#,n]b,m1]b
3>3>64>2=3[27,63]3=3[1,64]4
Graham's number=3[4,64]3
3>3>65>2=3[27,64]3
Read more > 
As you know, zootzoot is googol!1, zootzootplex is googolplex!1, and zootzootduplex is googolduplex!1. Then, we can see the rule:
Rule: ZootzootÎ± is googolÎ±!1 using hyperfactorial array notation, where Î± is any string while googolÎ± is welldefined.
The zootzootzootplex looks like the exception, but since googolzootplex is not defined, the rule is not applied to this.
Here are some numbers:
 zootzooti=(102^51)!1, derived from googoli.
 zootzootij=(104^52)!1, derived from googolij.
 zootzootiji=(106^53)!1, derived from googoliji.
 zootzootiv=(108^54)!1, derived from googoliv.
 zootzootv=(110^55)!1, derived from googolv.
 zootzootex=(120^60)!1, derived from googolex.
 zootzootbang=((10^100)!)!1, derived from googolbang.
 zootzootding=(10^500)!1, derived from goâ€¦

Many googol series articles have the link to this page, but actually, it's outdated. So, I'm going to summarize the new "improved" page.
The definition of Ackermann's Generalized Exponential Notation, which is used throughout the page, says:
g(0, a, b) = b + a (addition) g(1, a, b) = ab = a*b = a++b (multiplication) g(2, a, b) = b^{a} = a^b = aâ†‘b = a**b = a+++b (exponentiation) g(3, a, b} = ^{a}b = a^^b = aâ†‘â†‘b (tetration) g(a, 0, 1) = 1 (zeroth power) g(c, 0, a) = 1 (zeroth operation) g(a, b, c) = g(a  1, g(a 1 , b, c) , c) (expansion) g(a, b, c, d) = g(a  1, b, c, g(b, c, d)) (nesting about base number) g(a, b, c, d, e) = g(a  1, b, g(c, d, e), e) (nesting about power number) g(a, b, c, d., e, f) = g(a  1, b, c, g(d, e, f), e, f) (nesting abouâ€¦
Read more > 
SIR(1,n,d) is exactly d and you cannot go higher. Here's the proof:
There is a theorem that if a polynomial has only integer coefficients, all the coefficients of the factors of it are integers.
If an equation whose root goes higher than d (let it e), the absolute value of the of the constant term of the original equation must be e or greater.
The exception to the statement above is when one of the roots is zero but in that case, you can divide the whole equation by x and start it over.
Anyway, the absolute value of the constant term (or the lowest nonzero term) must be e or greater, which means it is bigger than d.
It's a contradiction because we can only use the integer between d and d for the original coefficients.
Therefore, the absolute oâ€¦
Read more > 
0 1 2 3 4 5 6 7 8 9
2.001687
2.003536
2.005359
2.007157
2.008930
2.010680
2.012406
2.014109
2.015790
2.017450
2.019088
2.020705
2.022302
2.023879
2.025437
2.026976
2.028496
2.029998
2.031482
2.032949
2.034398
2.035831
2.037248
2.038648
2.040033
2.041403
2.042757
2.044097
2.045422
2.046733
2.048030
2.049313
2.050583
2.051839
2.053083
2.054314
2.055533
2.056739
2.057933
2.059116
2.060286
2.061446
2.062594
2.063731
2.064858
2.065974
2.067079
2.068174
2.069259
2.070334
2.071399
2.072455
2.073501
2.074538
2.075566
2.076584
2.077594
2.078595
2.079588
2.080572
2.081547
2.082515
2.083474
2.084426
2.085369
2.086305
2.087233
2.088154
2.089067
2.089973
2.090872
2.091764
2.092649
2.093527
2.094398
2.095262
2.096120
2.096971
2.097816
2.098655
2.099487
2.100313
2.101133
2.101947
2.102755
2.103557
2.104354
2.105144
2.105930
2.106709
2.107483
2.â€¦
Read more >